KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN TAMU DI CLUB LOUNGE PADMA RESORT LEGIAN, BALI - Marthasaputra, Nova Bagus; Andayani, Ni Luh Henny; Parma, I Putu Gede (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to describe the quality of service in improving guest satisfaction at Club Lounge Padma Resort Legian using qualitative methods. The discussion of the study leads to an explanation related to important factors in the service provided in improving the quality of service and guest satisfaction and what efforts need to be made to maintain the quality of service and guest satisfaction. The data collection methods used in this study were interviews, observations, and documentation. Interviews were conducted with staff, and using guest comment data. the results of this study indicate that by implementing important elements of service quality in accordance with the established SOP but there are still reviews of services and facilities that are considered lacking according to guests, further efforts that need to be made are to provide routine training to improve communication, friendliness and technical skills and plan routine evaluation briefing strategies and add facilities and improve the quality of food and beverages. Friendliness, politeness, responsiveness to guest needs, providing guarantees to guests, and staff reliability are important factors in service quality.